2011
DOI: 10.1523/jneurosci.2808-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic Drugs Rapidly Induce Dopamine Neuron Depolarization Block in a Developmental Rat Model of Schizophrenia

Abstract: Repeated administration of antipsychotic drugs to normal rats has been shown to induce a state of dopamine neuron inactivation known as depolarization block, which correlates with the ability of the drugs to exhibit antipsychotic efficacy and extrapyramidal side-effects in schizophrenia patients. Nonetheless, in normal rats depolarization block requires weeks of antipsychotic drug administration, whereas schizophrenia patients exhibit initial effects soon after initiating antipsychotic drug treatment. We now r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
94
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(106 citation statements)
references
References 54 publications
11
94
1
Order By: Relevance
“…It is therefore likely that the effects of antipsychotic medications will vary based on the state of the dopamine system and expression of D2-like receptors. Indeed, we demonstrate a qualitatively different physiological response to selective D2-like ligands in the MAM-treated rat, consistent with recent studies (Valenti et al, 2011). Thus, the current results provide critical information regarding changes in dopamine system function in an animal model of schizophrenia and moreover demonstrate the importance of using appropriate animal models when examining potential mechanistic correlates of antipsychotic efficacy.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…It is therefore likely that the effects of antipsychotic medications will vary based on the state of the dopamine system and expression of D2-like receptors. Indeed, we demonstrate a qualitatively different physiological response to selective D2-like ligands in the MAM-treated rat, consistent with recent studies (Valenti et al, 2011). Thus, the current results provide critical information regarding changes in dopamine system function in an animal model of schizophrenia and moreover demonstrate the importance of using appropriate animal models when examining potential mechanistic correlates of antipsychotic efficacy.…”
supporting
confidence: 89%
“…Indeed, here, we demonstrate enduring changes in dopamine D2 receptor function in a rodent model of schizophrenia that probably affect the response to antipsychotic medications. Furthermore, a recent study has demonstrated that MAM-treated rats display electrophysiological responses to both first-and second-generation antipsychotics that are qualitatively different from those observed in normal animals (Valenti et al, 2011). Thus, the presence of an augmented dopamine system may actually sensitize the system to facilitate antipsychotic-induced depolarization block of dopamine neurons.…”
mentioning
confidence: 98%
“…However, one hypothesis (Lodge and Grace 2011) suggests that psychosis results from hyperactivity in hippocampal subfields that excite the nucleus accumbens, which inhibits the ventral pallidum, and thereby disinhibits mesolimbic dopamine neurons. Accordingly, rats in a developmental model of schizophrenia had constitutively high levels of mesolimbic dopamine neuron population activity and exhibited depolarization block when antipsychotic drugs were administered acutely (Valenti et al 2011), which does support a role for depolarization block in the therapeutic benefits of antipsychotics. The availability of sodium channels largely determines whether a neuron will continue spiking versus entering depolarization block; thus the effect of antipsychotic drugs may be exerted at least in part through their effects on sodium channel availability.…”
Section: Discussionmentioning
confidence: 99%
“…Given similar deficits in anatomical, behavioral, neurophysiological, and now molecular markers, the MAM model is an exceptionally well-validated model with the potential to aid in preclinical drug discovery and development. Indeed, the MAM model has provided insight into therapeutic approaches such as the rapid onset of antipsychotic drug action (Valenti et al, 2011) and identification of novel targets, such as positive allosteric modulators selective for the a5-subunit of the GABA A receptor .…”
mentioning
confidence: 99%